Engineering Evaluation of Laterite Derived from Sedimentary Rock for Use as Subgrade and Sub-Base Materials - Ajayi, Owolabi; Konwea, Charles I.; Adesanya, Oluseyi O. (MO.RI Publishing, 2024)
Geotechnical assessment of lateritic soils obtained from along the Ojota and Shagamu ends of the Lagos–Ibadan expressway was conducted to evaluate their suitability for use as sub-grade and sub-base materials. Laboratory tests, including moisture content, specific gravity, particle size distribution, fabric/plasticity, compaction, and California Bearing Ratio (CBR), were performed on eight (8) soil samples following British Standards (BS) 1377 methods for soil testing. The lateritic soils were classified as clayey sand, silty clay, and silty to clayey sand. They exhibited moderate plasticity and semi-pervious characteristics, suggesting suitability for use as sub-grade materials. Samples 3, 5, 7, and 8 were identified as more suitable for road construction materials, while Samples 1, 2, 4, and 6 showed susceptibility to seasonal volume changes due to high clay content. These samples would require minor soil stabilization to mitigate the effects of their active clay contents. Adequate drainage systems were recommended to prevent water accumulation, soil volume changes, loss of load-bearing capacity, and potential material failure beneath road pavements. The geotechnical properties of the lateritic soils from the tropical area of Ojota–Shagamu differed significantly from those of other lateritic soils found in southwestern Nigeria.